Effects of Different Sources of Calcium in the Diet on Growth Performance, Blood Metabolic Parameters, and Intestinal Bacterial Community and Function of Weaned Piglets - Yang, Anqi; Wang, Kaijun; Peng, Xiaomin; Lv, Feifei; Wang, Ying; Cui, Yao; Wang, Yuhan; Qu, Dongshuai; Zhou, Jianqun; Si, Hongbin (Frontiers in Nutrition, 2022)
Despite a well-documented effect of calcium on the pig intestinal microbiota composition less is it yet known about changes in microbial functional properties or the effect of different sources of calcium. This experiment was conducted to study the effects of dietary calcium from different sources on production performance, immune indexes, antioxidant capacity, serum biochemical indexes and intestinal microflora of weaned pigs. A total of one thousand weaned piglets were randomly allocated to five groups (ten replicate pens per treatment with twenty piglets per pen) and fed diets supplemented with calcium carbonate, calcium citrate, multiple calcium, organic trace minerals and different concentrations of acidifier. The results showed that, the replacement of calcium carbonate by calcium citrate and multiple calcium had almost no significant effect on the growth of piglets compared with the control group, only diet of multiple calcium dramatically decreased the ADFI compared to the calcium citrate diet on day 15-28 (p < 0.05). The 5 groups did not change the content of MDA, SOD and GSH-Px (p > 0.10). A similar situation occurs in immune function of blood, there was no significant difference in immune indexes (IgG, IgA and IgM) among different treatments after weaning six weeks for piglets (p > 0.10). The 16S rRNA sequencing of ileal and cecal microbiota revealed that only the relative abundance of Actinobacteriota at the phyla level was greater significantly in the ileum of the A group compared to others’ group (p < 0.05). There were clear differences on seven bacteria in top 30 genera of ileum and cecum for five groups (p < 0.05). Metagenomic predictions by PICRUSt suggested that the intestinal microbiota was mainly involved in carbohydrate metabolism, amino acid metabolism, membrane transport and metabolism of cofactors and vitamins. Besides, adding calcium citrate to weaned piglet diet is better than other choices from the third week to the fourth week.